PENGARUH MEDIA E-BOOKLET 3 IN 1 TERHADAP PENGETAHUAN KONSUMSI JAJANAN SEHAT UPAYA PENCEGAHAN DIABETES MELITUS - Kalyavedarana, Larenthya; Sudiyat, Rahmat (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Non-communicable diseases are one of the leading causes of death in Indonesia. One of the main non-communicable diseases is diabetes mellitus. Data on diabetes mellitus in Indonesia in 2018 amounted to 1,017,290 cases. In 2022, the West Java Health Office found a total of 644,704 people with diabetes cases. The prevalence of DM cases in Purwakarta district is 12,446 people, while cases in Purwakarta sub-district are 2,682 cases. Riskesdas shows that the proportion of diabetes mellitus in children aged ≥15 years and older reaches 159,014 people with diabetes mellitus. Objective: To determine the influence of 3 in 1 e-booklet media on knowledge about snack consumption in efforts to prevent diabetes at SMPN 1 Purwakarta. Methods: The study used a quantitative method with a PPE media development model and a one-group pretest-posttest design. The number of samples was 87 students of SMPN 1 Purwakarta, the sampling technique used probability sampling. Results: The study using the Wilcoxon Signed Rank Test was obtained through a comparison of pretest and posttest scores in the invergence group which showed a p value of 0.000 < 0.05. Conclusion: There was a significant increase in knowledge between before and after the intervention through the 3-in-1 e-booklet media on the knowledge of SMPN 1 Purwakarta students about healthy snack consumption.